2009
DOI: 10.1111/j.1651-2227.2009.01494.x
|View full text |Cite
|
Sign up to set email alerts
|

Preschool children in need of special support: prevalence of traditional disability categories and functional difficulties

Abstract: Undiagnosed and diagnosed children share the same type of difficulties. Thus, in estimating the prevalence of children in need of special support in a preschool context, traditional disability categories capture only a small proportion of the children experiencing difficulties. Therefore, a functional approach in studies of children in need of special support is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 15 publications
2
30
0
2
Order By: Relevance
“…Studying individual behaviours gives a more detailed picture, and presents an opportunity to identify children at risk for future mental health problems (6) . Earlier research has also identified a positive relationship between satisfactory functioning and children´s engagement (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Studying individual behaviours gives a more detailed picture, and presents an opportunity to identify children at risk for future mental health problems (6) . Earlier research has also identified a positive relationship between satisfactory functioning and children´s engagement (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Children's right to support is further reinforced in the revised version of the national preschool curriculum (Swedish National Agency for Education, 2010). However, as mentioned earlier, actually not all of them do receive enough support to promote engagement in preschool (Lillvist and Granlund, 2010;Lundqvist et al, 2016;Almqvist et al, 2018). In addition, the Swedish Schools Inspectorate (Skolinspektionen, 2017) reported that about 2/3 of inspected preschools had shortcomings in their work related to special support.…”
Section: Support To Children In Swedish Preschoolsmentioning
confidence: 99%
“…Their different educational and professional backgrounds and focus tend to interfere when planning and implementing support. Moreover, studies (Lillvist and Granlund, 2010;Almqvist et al, 2018) have found that children in need of special support without a formal identification of the needs (i.e., a medical diagnosis) were provided with support only by initiatives from the preschool staff. Children that were formally identified, on the other hand, were provided with support from professionals in the preschool support team, child healthcare, or habilitation team.…”
Section: Support To Children In Swedish Preschoolsmentioning
confidence: 99%
See 2 more Smart Citations